Yeasts isolated from fermenting juice extracted from white-wine grape varieties in Zulia state, Venezuela - Araujo, S.; Ferrer, A.; Sulbarán de Ferrer, B.; Nava, C.; Ojeda de Rodríguez, G.; Nava, R. A. (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2012)
Wine making in Zulia State, Venezuela, has been steadily increasing for the past few years. One of the goals is to produce wine with regional characteristics, and one of the approaches is to use endogenous yeasts well adapted to the environment. A total of 191 isolated yeasts were obtained from fermenting juice extracted from the white-wine grape varieties French colombard and Ugni blanc, 43 of which were identified. Standard plate and broth techniques were used for morphology, colony aspect, pigment production and formation of pseudomycelium and true mycelium. Ascospore formation, together with sugar fermentation and carbon and nitrogen asimilation studies, were used for yeast identification. Genera found in both varieties were Candida, Pichia, Brettanomyces, Zygosaccharomyces and Saccharomyces. Kloeckera and Schizosaccharomyces were only isolated from French colombard. All isolated species are related to wine making, some of them with undesirable properties and others with desirable ones, among which Saccharomyces rouxii and S. cerevisiae species look the most promising.